The Territory of the NATO - Matthijs, Herman (Advances in Social Sciences Research Journal, 2022)
With the demands from Finland and Sweden to join the NATO (North Atlantic Treaty Organization) and the Russian military invasion of Ukraine the public opinion and media are often relating to the borders of this Western military alliance. This article analyses the territory of the NATO.